Preparation method of fiber with efficient photo-thermal heating and heat preservation functions
By using Cu2S micro-nano hybrid particles in the fiber and combining template load growth method and in-situ polymerization technology, the problem of poor dispersion of Cu2S in the fiber is solved, and fiber preparation with high-efficiency photothermal heating and insulation functions is achieved.
Patent Information
- Application Number
- CN202411627326.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-11
AI Technical Summary
Cu2S has poor dispersion in fibers and is prone to agglomeration to form large particles, affecting the mechanical properties and comfort of the fibers.
By selecting Cu2S micro-nano hybrid particles as photothermal particles, ultra-small micro-nano hybrid particles with ultra-small particle size are prepared by template load growth method and wet grinding technology, and combined with PET composite materials through in-situ polymerization to improve Cu2S Dispersion and compatibility in fiber matrix.
The uniform dispersion of Cu2S in the fiber is achieved, the photothermal conversion efficiency, durability and mechanical properties of the fiber are improved, and the fiber has a rapid heating and long-term stable insulation function.
Smart Images

Figure CN119411247A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fiber manufacturing technology, and in particular to a method for preparing a fiber having both efficient photothermal heating and heat preservation functions. Background Art
[0002] Current thermal regulation textiles generally achieve heating and heat preservation by coating functional materials on the fiber surface. These traditional methods mainly include coating method, composite fiber method and doping method. However, these methods have some defects, which limit the breadth and effectiveness of their practical application.
[0003] The coating method is simple but has poor durability and affects comfort; the composite fiber method improves durability and comfort but has a complex process, high cost and poor dispersion; the doping method improves uniformity but has poor compatibility and can easily reduce fiber performance. Currently, common photothermal materials are mainly inorganic nanomaterials (such as copper oxide, iron oxide, etc.) and organic materials (carbon nanotubes, graphene, etc.), each of which has different advantages and disadvantages. Inorganic nanomaterials have high photothermal conversion efficiency, but poor dispersion in fibers, and are easily aggregated to form large particles, affecting the mechanical properties and comfort of the fibers. Organic photothermal materials are easier to combine with fibers, but have low photothermal conversion efficiency and poor durability. At the same time, due to the dark color, it is not conducive to subsequent processing.
[0004] In order to overcome these shortcomings, researchers are committed to developing new photothermal functional materials and preparation methods to improve the photothermal conversion efficiency and durability of fibers. Among them, Cu2S (copper sulfide), as a new photothermal material, shows many unique advantages and advancements such as high photothermal conversion efficiency, good chemical stability and far-infrared emission performance. However, Cu2S has poor dispersion in fibers and is easy to aggregate to form large particles. Summary of the invention
[0005] The present application provides a method for preparing fibers with both efficient photothermal heating and thermal insulation functions, which can be used to solve the problem that Cu2S has poor dispersion in the fiber and is easy to aggregate to form large particles, ensuring that the material has high light absorption and heating performance, and has good breaking strength, weaving characteristics and excellent wash resistance.
[0006] A method for preparing a fiber with both efficient photothermal heating and heat preservation functions, wherein Cu2S micro-nano hybrid particles are selected as photothermal particles, and the high photothermal conversion efficiency and good chemical stability of the particles are utilized to ensure that the material has the performance of rapid heating and long-term stability; in order to improve the dispersibility and compatibility of the photothermal particles in the fiber matrix, a one-dimensional / two-dimensional micron-sized material containing metal ions in the skeleton and hydroxyl groups on the surface is used as a template, a multifunctional chelating agent is used to chelate copper ions on the template surface, and a sulfur source is simultaneously introduced to prepare ultra-small particle size Cu2S micro-nano hybrid particles, and a highly dispersed ethylene glycol slurry is prepared by wet grinding; the slurry is used to perform in-situ polymerization with PTA to prepare PET / Cu2S with efficient photothermal heating. 2-x The S nanocomposite material was finally prepared into a hollow fiber with both heating and heat preservation functions through melt spinning.
[0007] Furthermore, the preparation method of the high-efficiency photothermal heating and heat preservation functional fiber specifically comprises the following steps:
[0008] Step 1, preparing ultra-small-sized Cu2S micro-nano hybrid particles: dispersing the template particles in an aqueous solution, adding a chelating agent and a copper source, and then adding a sulfur source, and obtaining ultra-small-sized Cu2S micro-nano hybrid particles after reaction;
[0009] Step 2, preparing Cu2S micro-nano hybrid particle ethylene glycol slurry: weighing Cu2S micro-nano hybrid particles, adding them, ethylene glycol and dispersant in proportion to a wet grinding device, adjusting the process for grinding, and obtaining Cu2S micro-nano hybrid particle ethylene glycol slurry after grinding;
[0010] Step 3, PET / Cu 2-x Preparation of Cu2S nanocomposite materials: The ethylene glycol slurry of Cu2S micro-nano hybrid particles, PTA, ethylene glycol and catalyst were added into the polymerization reactor in proportion to prepare PET / Cu2S nanocomposite materials by in-situ polymerization. 2-x S nanocomposites;
[0011] Step 4: Preparation of fiber with high-efficiency photothermal heating and heat preservation functions: Prepare PET / Cu 2-x The S nanocomposite material and PET are mixed in proportion and then melt-spinned to prepare a light-absorbing, heat-generating and heat-insulating dual-functional fiber with high hollowness.
[0012] Preferably, in step 1, the size of the one-dimensional / two-dimensional micron-scale template is 2 to 80 μm.
[0013] Preferably, in step 1, the template is one or more of zirconium phosphate, montmorillonite, layered metal oxide, layered double metal hydroxide, and halloysite nanotube.
[0014] Preferably, in step 1, the copper source is one or more of copper chloride, copper sulfate, copper nitrate and copper acetate; the chelating agent is one or more of aminotriacetic acid, ethylenediamine disuccinic acid, diethylenetriaminepentaacetic acid, ethylenediaminetetraacetic acid, triammonium citrate and trisodium citrate; the sulfur source is one or more of sodium sulfide, ammonium sulfide, barium sulfide and calcium sulfide.
[0015] Preferably, in step 1, the concentration of the template aqueous solution is 10-500 g / ml, and the ratio of the template to the copper source, the chelating agent, and the sulfur source is 1 g: (0.002-0.008) mol: (0.001-0.002) mol: (0.002-0.008) mol; the reaction conditions are a reaction temperature of 40-75°C and a reaction time of 2-6 hours; and the particle size of the ultra-small particle size of Cu2S is 5-20 nm.
[0016] Preferably, in step 2, the mass ratio of ethylene glycol to Cu2S micro-nano hybrid particle dispersant in the Cu2S micro-nano hybrid particle ethylene glycol slurry is 1:0.15-2:0.0075-1; the grinding speed of the grinder is 4000-7000r / min, and the grinding time is 8-10h; the dispersant is one or more of polyvinyl pyrrolidone, polyethylene glycol, polyacrylic acid, sodium polystyrene sulfonate, polylysine, and polyoxyethylene-polyoxypropylene copolymer, and the particle size of the Cu2S micro-nano hybrid particles is 100-500nm.
[0017] Preferably, in step 3, the preparation of PET / Cu 2-x The ratio of Cu2S micro-nano hybrid particle ethylene glycol slurry to terephthalic acid and ethylene glycol antimony required for the S nanocomposite material is 1:1.5-1.7:0.0008-0.001; the reaction conditions are 180-220°C for a reaction time of 2-3h, and 270-285°C for a reaction time of 1-1.5h.
[0018] Preferably, in step 4, the PET / Cu 2-x The mass ratio of S nanocomposite material to PET slice is 1:4-39; the hollow shape is double C hollow, and the hollowness is 30%-35%; the spinning condition is that the winding speed is 2800-5000m / min.
[0019] Preferably, in step 4, the fiber having both efficient photothermal heating and heat preservation functions has a fineness of 30-150d, a fiber number of 24-144, and a strength of 3.2-4.0cN / dtex.
[0020] Preferably, in step 4, the fiber with both efficient photothermal heating and thermal insulation functions has a light absorption temperature rise of 10-20°C, a far-infrared emissivity of 0.9-0.98, a far-infrared radiation temperature rise of 2.0-3.0°C, and is washable for more than 50 times.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] High photothermal conversion efficiency: Cu2S nanomaterials have high photothermal conversion efficiency and can effectively convert absorbed light energy into thermal energy to achieve rapid temperature rise. The present invention enables Cu2S to perform well in photothermal applications, especially for textiles that require rapid response.
[0023] Small particle size and uniform dispersion: Through the template-loaded growth method and wet grinding technology, Cu2S micro-nano hybrid particles with ultra-small particle size and high dispersion can be prepared. The preparation method of the present invention ensures that the Cu2S particles can be evenly dispersed in the fiber matrix, avoiding the problem of large particle aggregation and maintaining the softness and mechanical properties of the fiber.
[0024] Enhanced compatibility: The combination of in-situ polymerization and ethylene glycol slurry improves the compatibility of Cu 2-x The compatibility of S with the polyester matrix ensures the overall performance of the fiber. 2-x The S particles are evenly distributed in the polyester matrix, thereby improving the comprehensive properties of the composite material.
[0025] Good chemical stability: Cu2S material has good chemical stability, can maintain its light and thermal properties under different environmental conditions, and is not easily affected by external factors such as humidity and temperature, ensuring the long-term performance of the fiber material.
[0026] Heat preservation function: In addition to photothermal heating, Cu2S also has good far-infrared emission performance, which can effectively keep warm and further improve the functionality of the fiber. The present invention allows the fiber to maintain temperature while absorbing light and heating, providing a longer-lasting warming effect.
[0027] Good mechanical properties and durability: The hollow fibers prepared by melt spinning not only have efficient photothermal heating and heat preservation functions, but also maintain good breaking strength and weaving characteristics. At the same time, the washability of the fiber is also significantly improved, which enhances its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A flow chart of the method provided for this application.
[0029] Figure 2 This is a light absorption and heat generation diagram of the photothermal heating double C hollow fiber prepared in Example 1 provided in this application. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the present application clearer, the implementation methods of the present application will be further described in detail below with reference to the accompanying drawings.
[0031] The method provided by the present invention uses a one-dimensional / two-dimensional micron-sized material containing metal ions in the skeleton and hydroxyl groups on the surface as a template, uses a multifunctional chelating agent to chelate copper ions on the template surface, and simultaneously introduces a sulfur source to prepare ultra-small particle size nano Cu2S; grinds the nano Cu2S with ethylene glycol and a dispersant to prepare a highly dispersed ethylene glycol slurry; uses the slurry to carry out in-situ polymerization with terephthalic acid (PTA) to prepare PET / Cu2S with high efficiency photothermal heating. 2-x S nanocomposite material; hollow fibers with high hollowness are prepared by melt spinning method.
[0032] The present invention adopts the following test methods to test the heating performance, breaking strength and washability:
[0033] Temperature rise performance: Under the conditions of temperature of (20±2)℃ and relative humidity of (65±2)%, use XR-3 light thermal storage performance tester and xenon arc lamp as the irradiation light source. Place the sample under a certain irradiation intensity. The sample absorbs light energy and causes the temperature to change. Use a temperature sensor to test the sample temperature. Record the temperature change of the sample at each time point within 10 minutes of irradiation and 10 minutes of turning off the light source. Calculate the maximum temperature rise value, average temperature rise value and test endpoint temperature rise value of the sample within 20 minutes.
[0034] Breaking strength: Use a tensile testing machine to test the breaking strength of high-efficiency photothermal heating and thermal insulation functional fibers according to ASTM D2256. After conditioning the fiber sample (length 250mm) at a temperature of (20±2)°C and a relative humidity of (65±5)% for 24 hours, clamp it between the clamps of the tensile testing machine, and set the stretching speed to 300mm / min. Start the testing machine and gradually increase the stress until the sample breaks, record the maximum load and elongation at break, and calculate the breaking strength. Repeat the test for at least 10 samples, and calculate the average breaking strength and standard deviation. Finally, generate a test report, record the test conditions, data, and analysis results to evaluate the mechanical properties of the fiber.
[0035] Washability: The high-efficiency photothermal heating and heat preservation functional fiber was tested for 50 washing cycles using a standard washing machine and a phosphorus-free detergent, and the sample was dried after each wash. After every 10 washes, the breaking strength of the sample was tested using a tensile testing machine according to the ASTM D2256 standard, and its photothermal heating performance was evaluated. The test results showed that after 50 washes, the breaking strength and photothermal heating performance of the fiber remained at a high level, indicating that the fiber has good washability.
[0036] The present application is further described below in conjunction with specific embodiments.
[0037] Example 1
[0038] (1) Preparation of ultra-small Cu2S micro-nano hybrid particles: 10 kg of template particles (zirconium phosphate, particle size 2 microns) were dispersed in 1000 ml of aqueous solution, 1 mol of chelating agent (aminotriacetic acid) and 2 mol of copper source (copper chloride) were added, and stirred evenly. 2 mol of sulfur source (sodium sulfide) was added, and the mixture was reacted at 40°C for 2 hours to obtain ultra-small Cu2S micro-nano hybrid particles (5 nm).
[0039] (2) Preparation of Cu2S micro-nano hybrid particle ethylene glycol slurry: Weigh 15 g of Cu2S micro-nano hybrid particles with a particle size of 100 nm, add them to a wet grinding device in proportion with 15 g of ethylene glycol and 0.75 g of a dispersant (polyvinyl pyrrolidone). The grinding device speed is set to 7000 r / min, and the grinding time is 10 hours to obtain a highly dispersed Cu2S micro-nano hybrid particle ethylene glycol slurry.
[0040] (3) Preparation of PET / Cu 2-x S nanocomposite material: ethylene glycol slurry of Cu2S micro-nano hybrid particles, 46.125g of terephthalic acid (PTA), 0.024g of ethylene glycol antimony and ethylene glycol were added into a polymerization reactor in proportion. The reaction was carried out at 180°C for 2 hours and then at 270°C for 1 hour to prepare PET / Cu2S nanocomposite material. 2-x S nanocomposite materials.
[0041] (4) Preparation of hollow fibers with efficient photothermal heating and heat preservation functions: PET / Cu 2-x The S nanocomposite material and PET chips were mixed in a mass ratio of 1:39, and double C hollow fibers with a hollowness of 30% were prepared by a melt spinning method. The spinning condition was set at a winding speed of 5000 m / min.
[0042] After testing, the prepared hollow fiber specifications are 40D / 36F, the strength is 2.6cN / dtex, after being washed 50 times, the temperature rises by 20°C after 20 minutes of illumination, the far-infrared emissivity is 0.98, and the radiation temperature rise can reach 3.0°C.
[0043] Example 2
[0044] (1) Preparation of ultra-small Cu2S micro-nano hybrid particles: 10 kg of template particles (zirconium phosphate, particle size 2 microns) were dispersed in 1000 ml of aqueous solution, 2 mol of chelating agent (aminotriacetic acid) and 8 mol of copper source (copper chloride) were added, and stirred evenly. 8 mol of sulfur source (sodium sulfide) was added, and the mixture was reacted at 75°C for 6 hours to obtain ultra-small Cu2S micro-nano hybrid particles (20 nm).
[0045] (2) Preparation of Cu2S micro-nano hybrid particle ethylene glycol slurry: Weigh 15 g of Cu2S micro-nano hybrid particles with a particle size of 500 nm, add them to a wet grinding device in proportion with 30 g of ethylene glycol and 15 g of a dispersant (polyvinyl pyrrolidone). The grinding device speed is set to 4000 r / min, and the grinding time is 8 hours to obtain a highly dispersed Cu2S micro-nano hybrid particle ethylene glycol slurry.
[0046] (3) Preparation of PET / Cu 2-x S nanocomposite material: ethylene glycol slurry of Cu2S micro-nano hybrid particles, 102g of terephthalic acid (PTA), 0.06g of ethylene glycol antimony and ethylene glycol were added into a polymerization reactor in proportion. The reaction was carried out at 220°C for 3 hours and then at 285°C for 1.5 hours to prepare PET / Cu2S nanocomposite material. 2-x S nanocomposite materials.
[0047] (4) Preparation of hollow fibers with efficient photothermal heating and heat preservation functions: PET / Cu 2-x The S nanocomposite material was mixed with PET chips in a mass ratio of 1:4, and double C hollow fibers with a hollowness of 35% were prepared by melt spinning. The spinning conditions were set at a winding speed of 2800 m / min.
[0048] After testing, the prepared hollow fiber specifications are 40D / 36F, the strength is 2.8cN / dtex, after being washed 50 times, the temperature rises by 10°C after 20 minutes of illumination, the far-infrared emissivity is 0.9, and the radiation temperature rise can reach 2.0°C.
[0049] Example 3
[0050] (1) Preparation of ultra-small Cu2S micro-nano hybrid particles: 10 kg of template particles (zirconium phosphate, particle size 2 microns) were dispersed in 1000 ml of aqueous solution, 1 mol of chelating agent (ethylenediamine disuccinic acid) and 8 mol of copper source (copper sulfate) were added, and stirred evenly. 2 mol of sulfur source (barium sulfide) was added, and the mixture was reacted at 40°C for 2 hours to obtain ultra-small Cu2S micro-nano hybrid particles (20 nm).
[0051] (2) Preparation of Cu2S micro-nano hybrid particle ethylene glycol slurry: Weigh 15 g of Cu2S micro-nano hybrid particles with a particle size of 100 nm, add them to a wet grinding device in proportion with 100 g of ethylene glycol and 0.75 g of a dispersant (polyvinyl pyrrolidone). The grinding device speed is set to 7000 r / min, and the grinding time is 10 hours to obtain a highly dispersed Cu2S micro-nano hybrid particle ethylene glycol slurry.
[0052] (3) Preparation of PET / Cu 2-x S nanocomposite material: ethylene glycol slurry of Cu2S micro-nano hybrid particles, 23.44g of terephthalic acid (PTA), 0.0219g of ethylene glycol antimony and ethylene glycol were added into a polymerization reactor in proportion. The reaction was carried out at 180°C for 2 hours and then at 270°C for 1 hour to prepare PET / Cu2S nanocomposite material. 2-x S nanocomposite materials.
[0053] (4) Preparation of hollow fibers with efficient photothermal heating and heat preservation functions: PET / Cu 2-x The S nanocomposite material and PET chips were mixed at a mass ratio of 1:30, and double C hollow fibers with a hollowness of 30% were prepared by a melt spinning method. The spinning condition was set at a winding speed of 2800 m / min.
[0054] After testing, the prepared hollow fiber specifications are 40D / 36F, the strength is 2.5cN / dtex, after being washed 50 times, the temperature rises by 14°C after 20 minutes of illumination, the far-infrared emissivity is 0.93, and the radiation temperature rise can reach 2.6°C.
[0055] Example 4
[0056] (1) Preparation of ultra-small Cu2S micro-nano hybrid particles: 500 kg of template particles (zirconium phosphate, particle size 2 microns) were dispersed in 1000 ml of aqueous solution, 1000 mol of chelating agent (ethylenediamine disuccinic acid) and 4000 mol of copper source (copper sulfate) were added, and stirred evenly. 4000 mol of sulfur source (barium sulfide) was added, and the mixture was reacted at 75°C for 6 hours to obtain ultra-small Cu2S micro-nano hybrid particles (20 nm).
[0057] (2) Preparation of Cu2S micro-nano hybrid particle ethylene glycol slurry: Weigh 15 g of Cu2S micro-nano hybrid particles with a particle size of 500 nm, add them to a wet grinding device in proportion with 7.5 g of ethylene glycol and 7.5 g of a dispersant (polyvinyl pyrrolidone). The grinding device speed is set to 4000 r / min, and the grinding time is 8 hours to obtain a highly dispersed Cu2S micro-nano hybrid particle ethylene glycol slurry.
[0058] (3) Preparation of PET / Cu 2-xS nanocomposite material: ethylene glycol slurry of Cu2S micro-nano hybrid particles, 26.54g of terephthalic acid (PTA), 0.0274g of ethylene glycol antimony and ethylene glycol were added into a polymerization reactor in proportion. The reaction was carried out at 220℃ for 3 hours and then at 285℃ for 1.5 hours to prepare PET / Cu2S nanocomposite material. 2-x S nanocomposite materials.
[0059] (4) Preparation of hollow fibers with efficient photothermal heating and heat preservation functions: PET / Cu 2-x The S nanocomposite material and PET chips were mixed in a mass ratio of 1:29, and double C hollow fibers with a hollowness of 35% were prepared by a melt spinning method. The spinning condition was set at a winding speed of 2800 m / min.
[0060] After testing, the prepared hollow fiber specifications are 40D / 36F, the strength is 2.6cN / dtex, after being washed 50 times, the temperature rises by 16°C after 20 minutes of illumination, the far-infrared emissivity is 0.93, and the radiation temperature rise can reach 2.4°C.
[0061] Example 5
[0062] (1) Preparation of ultra-small Cu2S micro-nano hybrid particles: 10 kg of template particles (zirconium phosphate, particle size 2 microns) were dispersed in 1000 ml of aqueous solution, 1 mol of chelating agent (aminotriacetic acid) and 2 mol of copper source (copper chloride) were added, and stirred evenly. 2 mol of sulfur source (sodium sulfide) was added, and the mixture was reacted at 45°C for 2 hours to obtain ultra-small Cu2S micro-nano hybrid particles (5 nm).
[0063] (2) Preparation of Cu2S micro-nano hybrid particle ethylene glycol slurry: Weigh 15 g of Cu2S micro-nano hybrid particles with a particle size of 100 nm, add them to a wet grinding device in proportion with 100 g of ethylene glycol and 0.75 g of a dispersant (polyvinyl pyrrolidone). The grinding device speed is set to 7000 r / min, and the grinding time is 10 hours to obtain a highly dispersed Cu2S micro-nano hybrid particle ethylene glycol slurry.
[0064] (3) Preparation of PET / Cu 2-x S nanocomposite material: ethylene glycol slurry of Cu2S micro-nano hybrid particles, 23.44g of terephthalic acid (PTA), 0.0219g of ethylene glycol antimony and ethylene glycol were added into a polymerization reactor in proportion. The reaction was carried out at 200℃ for 2 hours and then at 280℃ for 1 hour to prepare PET / Cu2S nanocomposite material. 2-x S nanocomposite materials.
[0065] (4) Preparation of hollow fibers with efficient photothermal heating and heat preservation functions: PET / Cu 2-xThe S nanocomposite material and PET chips were mixed at a mass ratio of 1:35, and double C hollow fibers with a hollowness of 30% were prepared by melt spinning. The spinning condition was set at a winding speed of 5000 m / min.
[0066] After testing, the prepared hollow fiber specifications are 40D / 36F, the strength is 2.8cN / dtex, after being washed 50 times, the temperature rises by 18°C after 20 minutes of illumination, the far-infrared emissivity is 0.96, and the radiation temperature rise can reach 2.8°C.
[0067] Example 6
[0068] (1) Preparation of ultra-small Cu2S micro-nano hybrid particles: 500 kg of template particles (zirconium phosphate, particle size 2 microns) were dispersed in 1000 ml of aqueous solution, 1000 mol of chelating agent (aminotriacetic acid) and 4000 mol of copper source (copper sulfate) were added, and stirred evenly. 4000 mol of sulfur source (sodium sulfide) was added, and the mixture was reacted at 75°C for 6 hours to obtain ultra-small Cu2S micro-nano hybrid particles (20 nm).
[0069] (2) Preparation of Cu2S micro-nano hybrid particle ethylene glycol slurry: Weigh 15 g of Cu2S micro-nano hybrid particles with a particle size of 500 nm, add them to a wet grinding device in proportion with 7.5 g of ethylene glycol and 7.5 g of a dispersant (polyvinyl pyrrolidone). The grinding device speed is set to 4000 r / min, and the grinding time is 8 hours to obtain a highly dispersed Cu2S micro-nano hybrid particle ethylene glycol slurry.
[0070] (3) Preparation of PET / Cu 2-x S nanocomposite material: ethylene glycol slurry of Cu2S micro-nano hybrid particles, 26.54g of terephthalic acid (PTA), 0.0274g of ethylene glycol antimony and ethylene glycol were added into a polymerization reactor in proportion. The reaction was carried out at 200℃ for 3 hours and then at 280℃ for 1.5 hours to prepare PET / Cu2S nanocomposite material. 2-x S nanocomposite materials.
[0071] (4) Preparation of hollow fibers with efficient photothermal heating and heat preservation functions: PET / Cu 2-x The S nanocomposite material was mixed with PET chips at a mass ratio of 1:32, and double C hollow fibers with a hollowness of 35% were prepared by melt spinning. The spinning condition was set at a winding speed of 2800 m / min.
[0072] After testing, the prepared hollow fiber specifications are 40D / 36F, the strength is 2.5cN / dtex, after being washed 50 times, the temperature rises by 17.2°C after 20 minutes of illumination, the far-infrared emissivity is 0.95, and the radiation temperature rise can reach 2.8°C.
[0073] Example 7
[0074] (1) Preparation of ultra-small Cu2S micro-nano hybrid particles: 20 kg of template particles (zirconium phosphate, particle size 2 microns) were dispersed in 1000 ml of aqueous solution, 2 mol of chelating agent (aminotriacetic acid) and 4 mol of copper source (copper chloride) were added, and stirred evenly. 4 mol of sulfur source (sodium sulfide) was added, and the mixture was reacted at 50°C for 3 hours to obtain ultra-small Cu2S micro-nano hybrid particles (9 nm).
[0075] (2) Preparation of Cu2S micro-nano hybrid particle ethylene glycol slurry: Weigh 15 g of Cu2S micro-nano hybrid particles with a particle size of 100 nm, add them to a wet grinding device in proportion with 100 g of ethylene glycol and 0.95 g of a dispersant (polyvinyl pyrrolidone). The grinding device speed is set to 6000 r / min, and the grinding time is 10 hours to obtain a highly dispersed Cu2S micro-nano hybrid particle ethylene glycol slurry.
[0076] (3) Preparation of PET / Cu 2-x S nanocomposite material: ethylene glycol slurry of Cu2S micro-nano hybrid particles, 25.44g of terephthalic acid (PTA), 0.0234g of ethylene glycol antimony and ethylene glycol were added into a polymerization reactor in proportion. The reaction was carried out at 180°C for 2 hours and then at 270°C for 1 hour to prepare PET / Cu2S nanocomposite material. 2-x S nanocomposite materials.
[0077] (4) Preparation of hollow fibers with efficient photothermal heating and heat preservation functions: PET / Cu 2-x The S nanocomposite material and PET chips were mixed at a mass ratio of 1:25, and double C hollow fibers with a hollowness of 30% were prepared by a melt spinning method. The spinning condition was set at a winding speed of 4000 m / min.
[0078] After testing, the prepared hollow fiber specifications are 40D / 36F, the strength is 2.4cN / dtex, after being washed 50 times, the temperature rises by 19.2°C after 20 minutes of illumination, the far-infrared emissivity is 0.98, and the radiation temperature rise can reach 2.9°C.
[0079] This method can prepare ultra-small and highly dispersed Cu2S micro-nano hybrid particles through template-loaded growth method and wet grinding technology, avoiding defects that affect fiber softness and mechanical properties. Compared with organic materials, the in-situ polymerization of ethylene glycol slurry and polyester polymerization reactor ensures the uniform distribution of Cu2S particles in the polyester matrix, improves the compatibility of the material, and overcomes the problem of poor dispersion of traditional materials.
[0080] The above-described embodiments of the present application do not constitute a limitation on the protection scope of the present application.
Claims
1. A method for preparing a fiber with both efficient photothermal heating and heat preservation functions, characterized in that: The method comprises: Step 1, preparation of ultra-small Cu2S micro-nano hybrid particles: dispersing the template particles in an aqueous solution, adding a chelating agent and a copper source, and then adding a sulfur source, and obtaining ultra-small Cu2S micro-nano hybrid particles after reaction; Step 2, preparation of ethylene glycol slurry of Cu2S micro-nano hybrid particles: weigh Cu2S micro-nano hybrid particles, add ethylene glycol and dispersant in proportion to a wet grinding device, adjust the process for grinding, and obtain Cu2S micro-nano hybrid particle ethylene glycol slurry after grinding; Step 3, PET / Cu 2-x Preparation of Cu2S nanocomposite materials: The ethylene glycol slurry of Cu2S micro-nano hybrid particles, PTA, ethylene glycol and catalyst were added into the polymerization reactor in proportion to prepare PET / Cu2S nanocomposite materials by in-situ polymerization. 2-x S nanocomposites; Step 4: Preparation of fiber with high-efficiency photothermal heating and heat preservation functions: Prepare PET / Cu 2-x The S nanocomposite material and PET are mixed in proportion and then melt-spinned to prepare a light-absorbing, heat-generating and heat-insulating dual-functional fiber with high hollowness.
2. The method for preparing a fiber having both efficient photothermal heating and heat preservation functions according to claim 1, characterized in that: The size of the template is 2-80 μm, and the template is one or more of zirconium phosphate, montmorillonite, layered metal oxide, layered double metal hydroxide, and halloysite nanotube.
3. The method for preparing a fiber with both efficient photothermal heating and heat preservation functions according to claim 1, characterized in that: The copper source is one or more of copper chloride, copper sulfate, copper nitrate and copper acetate; the chelating agent is one or more of aminotriacetic acid, ethylenediamine disuccinic acid, diethylenetriaminepentaacetic acid, ethylenediaminetetraacetic acid, triammonium citrate and trisodium citrate; the sulfur source is one or more of sodium sulfide, ammonium sulfide, barium sulfide and calcium sulfide.
4. The method for preparing a fiber with both efficient photothermal heating and heat preservation functions according to claim 1, characterized in that: The concentration of the template aqueous solution is 10-500 g / ml, and the ratio of the template to the copper source, the chelating agent and the sulfur source is 1 g: (0.002-0.008) mol: (0.001-0.002) mol: (0.002-0.008) mol; the reaction conditions are a reaction temperature of 40-75° C. and a reaction time of 2-6 hours; and the particle size of the ultra-small Cu2S is 5-20 nm.
5. The method for preparing a fiber with both efficient photothermal heating and heat preservation functions according to claim 1, characterized in that: The mass ratio of ethylene glycol to the Cu2S micro-nano hybrid particle dispersant in the Cu2S micro-nano hybrid particle ethylene glycol slurry is 1:0.15-2:0.0075-1; the rotation speed of the grinder during grinding is 4000-7000 r / min, and the grinding time is 8-10 hours; the dispersant is one or more of polyvinyl pyrrolidone, polyethylene glycol, polyacrylic acid, sodium polystyrene sulfonate, polylysine, and polyoxyethylene-polyoxypropylene copolymer, and the particle size of the Cu2S micro-nano hybrid particles is 100-500 nm.
6. The method for preparing a fiber with both efficient photothermal heating and heat preservation functions according to claim 1, characterized in that: The preparation of PET / Cu 2-x The ratio of Cu2S micro-nano hybrid particle ethylene glycol slurry to terephthalic acid and ethylene glycol antimony required for the S nanocomposite material is 1:1.5-1.7:0.0008-0.001; the reaction conditions are 180-220°C for 2-3h and 270-285°C for 1-1.5h.
7. The method for preparing a fiber with both efficient photothermal heating and heat preservation functions according to claim 1, characterized in that: The PET / Cu 2-x The mass ratio of S nanocomposite material to PET slice is 1:4-39; the hollow shape is double C hollow, and the hollowness is 30%-35%; the spinning condition is that the winding speed is 2800-5000m / min.